Penerapan Pendekatan Ilmiah Dalam Mengajar Keterampilan Berbicara Dengan Menggunakan Lagu - Sukanta Sukanta (Holistik, 2022)
: On the teacher's side, the implementation of the 2013 curriculum includes a scientific approach, which is a more comprehensive approach at the stages of observing, questioning, associating / reasoning, gathering information and communicating. (Ministry of Education and Culture, 2014). The application of the scientific approach can be said to be a form of reform in the education sector. Reform that provides learning services and facilities to all students, where students can study in a learning environment that allows the development of knowledge, attitudes and skills. This approach aims to improve intellectual abilities, especially the thinking skills of high-level students, and shape students' ability to solve a problem systematically. In connection with these demands, the readiness of teachers to implement and apply them in the learning process is very important for the success of the scientific approach. Because no matter how ideal and good the educational curriculum is without being balanced with the ability of teachers to implement it, everything will be less meaningful (Sanjaya, 2010). From this statement, it can be concluded that the teacher's ability is the essence of the success of a lesson, both in the ability to plan and in implementing learning. Based on this, the authors are interested in conducting research with the title "Application of Scientific Approaches to Teaching Speaking Skills Using Songs in Eighth Grade MTS Al-Hidayah Dukupuntang"